The Effectiveness of Using Bingo Game in Teaching Vocabulary of the Eighth Grade Students at the SMP N 15 Purworejo in the Academic Year 2016/2017 - Erna Watiningsih (Scripta : English Department Journal, 2019)
Vocabulary is one of English components that must be taught to the students becausevocabulary has an important role for all language skills. But in teaching vocabulary, thestudents have difficulties in memorizing new words; so they lack of vocabulary. Theobjective of this research is to find out whether there is any effectiveness of using bingogame in teaching vocabulary to eight grade students of SMP N 15 Purworejo in academicyear 2016/2017.This research belongs to experimental research. This research wascarried out at SMP N 15 Purworejo. The total number of the population is 160 students.This research used 64 sample. To collect the data, the researcher used pre-test and posttest as the treatment. Then, the data result analyzed by using t-test formula.The resultof the mean of score of post test of experimental group is higher than control group(80.31 > 66.88). In addition, the result of t-value is 5.57. Then, the researcher conslutsthe critical value on the t-table using 5% (0.05) alpha level significance and the degree offreedom is 1.697. It means that that the use of bingo game in teaching vocabulary of atthe grade at the eighth grade students of SMP N 15 Purworejo in the academic year of2016/2017 is effective.